Treatment of Palm Oil Mill Effluent by an Integrated Aeration–Bipolar Electrocoagulation System - Febrianto Adi Nugroho; Handoko Rusiana Iskandar; Nadiem Anwar; Tiara Ariani Putri; Putu Teta Prihartini Aryanti (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2026)
Electrocoagulation (EC) has increasingly been used in wastewater treatment, including palm oil mill effluent (POME), due to its ease of operation and less sludge production. In this study, POME was treated using an integrated aeration and EC process, which was conducted continuously at a constant flow rate of 500 mL.min-1. The agitation process was applied in the EC reactor at a rotating speed of 20 rpm to shorten the electrolysis reaction time. The EC reactor was equipped with 6 electrodes as baffles. Two current densities (12 and 15A.m-2) and electrode configurations (3A-3C and 2A-2C-2B) were used, and the resulting effluents were compared. The experimental results showed that the highest contaminant removal was achieved with the electrode configuration 2A-2C-2B and the current intensity was 15 A. The BOD removal efficiency was 91.36% (from 132 to 11.4 mg.L-1), COD of 81.27% (from 386 to 72.3 mg.L-1), TDS of 47.64% (from 645.5 to 338 mg.L-1), TSS of 76.27% (from 43.7 to 10.4 mg.L-1), and turbidity of 96.46% (from 59.65 to 2.11 NTU). Meanwhile, the total energy requirement was 21.33 kWh.m-3 with the pH of the effluent of 8.05. The combination of aeration-EC can be used as an alternative POME treatment to achieve high contaminant removal efficiency.